Omega-3 as an Anti-Inflammatory Modality: Literature Review - Rachmat Hidayat; Nur Riviati (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Omega-3 fatty acids are polyunsaturated fatty acids that have multiple double bonds, the first double bond is located on the third carbon atom of the omega-methyl group, the next double bond is located at the third carbon atom from the previous double bond. The methyl omega group is the last group in the fatty acid chain. Omega-3 fatty acids are nutrients that play a vital role in the growth and development process of brain neuron cells for the intelligence of the born baby.